Pengembangan Sistem Rekomendasi Investasi Saham berbasis Web (Studi Kasus: Reliance Sekuritas Malang) - Vicky Melinda Tanto; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Stock investment recommendation is an activity of giving rating to stocks to determine whether the stocks are worth buying, holding, or selling. Stock investment recommendation is needed so that investors can invest with better considerations to their stock selection, and reduce risk of large financial losses. Stock investment recommendation are obtained by purchasing professional investment analyst services provided by securities companies. Reliance Securities Malang is a securities company that provides professional investment analyst services. The stock investment recommendation process is done by meeting in person, or online using a message exchange application, WhatsApp. One of the problems with the stock investment recommendation process is that the length of time required to produce an analysis is relatively lengthy, and by the time the analysis was given it may not apply to the latest stock price. A web-based stock recommendation system was developed to help with these problems. The system was developed using the waterfall model with an object-oriented approach. The system was implemented using several technologies: Typescript as the main development language, Express.js as the back-end framework, React.js as the front-end framework, and PostgreSQL as the database management system. The research resulted in analysis and specification of system requirements, design, system implementation and system testing results. The system is expected to be able to assist investors in their investment activities, as a consideration in selecting stocks